Bilateral breast cancer in China: A 10‐year single‐center retrospective study (2006–2016). (4th August 2021) - Jiang, Hanfang; Zhang, Ruyan; Liu, Xiaoran; Ran, Ran; Zhang, Jiayang; Liu, Yaxin; Gui, Xinyu; Chen, Yifei; Li, Kun; Shao, Bin; Yan, Ying; Liang, Xu; et al.
Abstract: Bilateral breast cancer (BBC) is an uncommon subset of breast cancer (BC), and it may present as synchronous bilateral breast cancer (sBBC) or metachronous bilateral breast cancer (mBBC). Through this study, we aimed to evaluate the proportion of BBC in BC and compare the clinicopathological characteristics, treatment, and outcomes of sBBC and mBBC at an academic cancer center in China. Patients with BC consecutively treated between 2006 and 2016 were retrospectively reviewed. Patients with BBC were included. In total, 3924 patients with BC were analyzed and 127 patients with BBC (28 sBBC, 99 mBBC) with a median follow‐up of 98 months were identified. The proportion of BBC was 3.2% (0.7%, sBBC; 2.5%, mBBC). The median age at the first diagnosis of mBBC was significantly younger than that at the first diagnosis of sBBC ( p = 0.027). Patients diagnosed as having sBBC were more likely to have a positive family history ( p = 0.047). The first tumors of mBBC were detected at a significantly earlier tumor stage compared with those of sBBC ( p = 0.028). The concordance rates of histopathologic type in the first and second tumors were 60.7% and 58.0% in sBBC and mBBC, respectively. sBBC had a significantly poorer disease‐free survival than mBBC did ( p = 0.001). BBC is a rare disease affecting the Chinese population. sBBC is associated with a greater prevalence of a family history of breast cancer and poorer prognosis, compared with mBBC.